PTU-307 The hidden endoscopic burden of sleeve gastrectomy and its comparison with roux-en-y gastric bypass. (22nd June 2015) - Arndtz, K; Steed, H; Hodson, J; Manjunath, S
Abstract : Introduction: In the UK, 61.9% of adults are obese and associated co-morbidity is estimated to cost the NHS £5 billion annually. 1 NICE recommends bariatric surgery as a treatment option for some obese patients. 2 Complications of bariatric surgery are commonly diagnosed and managed by the use of endoscopic procedures, such as endoscopic stent insertion or pneumatic balloon dilatation. This study aims to assess the burden of bariatric surgery-related endoscopy at our hospital, one of the main centres for bariatric surgery in the West Midlands. This is a parallel and enhanced study to "The Hidden Endoscopic burden of Roux-en-Y Gastric Bypass" (RYGB) published in Frontline Gastroenterology in 2013 3 and now also includes data for sleeve gastrectomy. Method: The retrospective study included all 211 patients undergoing sleeve gastrectomy over a 34 month period. We also utilised the previously collected data for the RYGB patient cohort which included 553 patients over 29 months. In both cohorts, the minimum follow up was 180 days. We searched our hospital endoscopic database for patients who underwent post-operative endoscopy for indications felt to be surgery related. Results: 16.6% of the sleeve gastrectomy patients required post-operative gastroscopy, of which 11.4% of procedures were therapeutic. This compares to 20.4% of the RYGB cohort of which 50.4% of procedures were therapeutic (p < 0.001). 1.9% of sleeve gastrectomy patients encountered a post-operative staple-line leak and collectively required 29 procedures including 8 stent insertions. One patient also developed stricturing (0.47%) requiring 18 pneumatic dilatations. 11.4% of the RYGB cohort developed an anastomotic stricture requiring 57 balloon dilatation procedures. To date, these procedures have accumulated a cost of £114, 458 in endoscopy tariffs, or £105 per RYGB and £267 per sleeve gastrectomy performed. Conclusion: Bariatric surgery can have significant complications in terms of patient morbidity and financial cost. Having a local bariatric surgery service increases the demand for endoscopic procedures in our hospital, both in investigating for and dealing with post-operative complications. Provision of extra resources and expertise needs to be taken into account. Disclosure of interest: None Declared. References: NICE Guidance 2014. Obesity: identification, assessment and management of overweight and obesity in children, young people and adults. CG189. London Department of Health Policy. Reducing obesity and improving diet. 2013. [Online]. Available from: https://www.gov.uk/government/policies/reducing-obesity-and-improving-diet [Accessed 1st July 2014] Steed H, Golar H, Manjunath S. The hidden endoscopic burden of Roux-en-Y gastric bypass surgery. Frontline Gastroenterol. 2013;4:69–72